2000
DOI: 10.1128/jvi.74.19.9234-9239.2000
|View full text |Cite
|
Sign up to set email alerts
|

Human Coronavirus 229E Infects Polarized Airway Epithelia from the Apical Surface

Abstract: Gene transfer to differentiated airway epithelia with existing viral vectors is very inefficient when they are applied to the apical surface. This largely reflects the polarized distribution of receptors on the basolateral surface. To identify new receptor-ligand interactions that might be used to redirect vectors to the apical surface, we investigated the process of infection of airway epithelial cells by human coronavirus 229E (HCoV-229E), a common cause of respiratory tract infections. Using immunohistochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
67
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 40 publications
8
67
0
Order By: Relevance
“…For example, we previously reported that human coronavirus (serotype 229E) efficiently transduces the apical surface of well-differentiated airway epithelia (28). In addition, respiratory syncytial virus and parainfluenza virus also have the capacity to enter polarized human airway epithelial cells through the apical surface (P. L. Sinn and P. B. McCray, unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
“…For example, we previously reported that human coronavirus (serotype 229E) efficiently transduces the apical surface of well-differentiated airway epithelia (28). In addition, respiratory syncytial virus and parainfluenza virus also have the capacity to enter polarized human airway epithelial cells through the apical surface (P. L. Sinn and P. B. McCray, unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
“…Primary lung and airway epithelial cell cultures have been used to investigate cellular responses to infection with many respiratory viruses, including influenza A virus (3,7,11,20,39,42,49,64,65,78,106,117,120,129), respiratory syncytial virus (RSV) (69,135), hantavirus (95), human coronaviruses (104,105,121), human parainfluenza virus type 3 (134), and adenovirus (85,86,110,131,132). Unlike conventional transformed cell lines, primary airway cultures, when differentiated fully, can mirror the in vivo tissue by being organized into a multilayered, polarized culture consisting of multiple cell types (7,42,85,110,117,134,135).…”
mentioning
confidence: 99%
“…Other viruses are known to efficiently infect the respiratory epithelium and have presumably evolved strategies to circumvent the glycocalyx barrier. Human coronaviruses, filoviruses, respiratory syncytial virus, and Sendai virus have improved gene transfer capacities for the airway epithelium after lumenal delivery compared to AdV (29,38,45,48). Further studies of the interactions of these enveloped viruses with the airway epithelium and a definition of how they circumvent the glycocalyx barrier may reveal mechanisms that will aid the development of improved vectors for the delivery of therapeutic transgenes to the lung epithelium.…”
Section: Discussionmentioning
confidence: 99%